ADMINISTRATIVE PERFORMANCE IN MANAGEMENT OF SCHOOL ASSETS ADMINISTRATIVENESS IN SEGERI 3 JUNIOR HIGH SCHOOL, BARRU DISTRICT - Sukmiah; Asriani; M, A.Pananrangi (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal